Simultaneous removal of toxic ammonia and lettuce cultivation in aquaponic system using microwave pyrolysis biochar - Su, Man Huan; Elfina, Azwar; Yang, Ya Feng; Sonne, Christian; Yek, Peter Nai Yuh; Liew, Rock Keey; Cheng, C. K.; Show, Pau Loke; Lam, Su Shiung (Elsevier Ltd, 2020)
This study examined an aquaponic approach of circulating water containing ammonia excretions from African catfish grown in an aquaculture tank for bacterial conversion into nitrates, which then acted as a nutrient substance to cultivate lettuce in hydroponic tank. We found that microwave pyrolysis biochar (450 g) having microporous (1.803 nm) and high BET surface area (419 m2/g) was suitable for use as biological carrier to grow nitrifying bacteria (63 g of biofilm mass) that treated the water quality through removing the ammonia (67%) and total suspended solids (68%), resulting in low concentration of remaining ammonia (0.42 mg/L) and total suspended solid (59.40 mg/L). It also increased the pH (6.8), converted the ammonia into nitrate (29.7 mg/L), and increased the nitrogen uptake by the lettuce (110 mg of nitrogen per plant), resulting in higher growth in lettuce (0.0562 %/day) while maintaining BOD5 level (3.94 mg/L) at acceptable level and 100% of catfish survival rate. Our results demonstrated that microwave pyrolysis biochar can be a promising solution for growing nitrifying bacteria in aquaponic system for simultaneous toxic ammonia remediation and generation of nitrate for growing vegetable in aquaculture industry.